PERBANDINGAN KERUSAKAN AKTUAL DAN PERKIRAAN PADA BANGUNAN TEMBOKAN TANPA PERKUATAN AKIBAT GEMPA - Jafar Jafar (TEKNISIA, 2021)
On April 18, 2018, an earthquake hit Banjarnegara Regency, Central Java. The earthquake was measured M4.4 at a depth of 4 km and caused damages to buildings in several villages within Kalibening District. Predicting the future earthquake events is difficult. However, it is possible to estimate the potential damage caused by an earthquake event. FEMA has developed a methodology called HAZUS to estimate the potential loss and damage caused by earthquakes. This study compared the level of actual damage to buildings subjected to the 2018 Banjarnegara earthquake with the estimated damage to buildings obtained using HAZUS. The real damage is obtained from the field survey while the estimated damage is obtained from the HAZUS modeling. The object of this research is the unreinforced masonry low-rise buildings (URML) in Kasinoman Village, one of the villages that suffered the most subjected to the 2018 Banjarnegara Earthquake. The result of this study indicates the actual damage has a higher mean damage ratio (20,40 %) compared to the estimated damage (11.66%). HAZUS is developed according to the performance and experimental data of the buildings in the US therefore it might not be compatible with the building in Indonesia, especially surveyed buildings in Banjarnegara. The reason is the buildings in the US fulfilled the earthquake-resistant building provision meanwhile the surveyed buildings did not.